Visibility, democratic public space and socially inclusive cities - Ceren Sezer (A+BE: Architecture and the Built Environment)
This research introduces the concept of visibility as a useful tool to assess the democratic features of public spaces. We understand democratic public spaces as open spaces, which are accessible to all and allow different cultural expressions for individuals and groups. The concept of visibility refers to the visual perception of the observable features of distinctive urban groups in public space, which give evidence of their lived experiences, and how they engage with, shape, and construct public space in everyday life. The main assumption of the study is that the visibility of distinctive urban groups on the street manifests the rights of these groups to participate in the public life of the city, which is a key feature of a democratic public space. Consequently, the presence and changes in the visibility of urban groups in public space is a highly political issue, which raises concerns in relation to just or unjust urban conditions.